Economic instruments for water management the cases of France, Mexico, and Brazil - Seroa da Motta, Ronaldo; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar, 2004)
This book argues that the economic appeal of using water charges to promote efficiency in usage and pollution control can be constrained by institutional and operational problems. Analysing the cases of France, Mexico and Brazil, the authors--respective local experts--illustrate that barriers are similar despite the existing differences among these economies.
1. Introduction -- 2. Conceptual framework and review of experiences -- 3. Country case : France -- 4. Country case : Mexico -- 5. Country case : Brazil -- 6. Conclusions.
Includes bibliographical references and index.
Keywords: Water-supply -- France -- Rates; Water consumption -- France; Water-supply -- Mexico -- Rates; Water consumption -- Mexico; Water-supply -- Brazil -- Rates; Water consumption -- Brazil; Electronic books